BLENDED TEACHING: COMBINING TRADITIONAL AND DIGITAL METHODS (Web of Teachers: Inderscience Research, 2025)
The teaching process is constantly developing and enriched with new methods and technologies. Traditional teaching methods are mainly based on the teacher presenting information and students receiving it. However, with the rapid development of digital technologies, new opportunities have appeared in the educational process. Blended learning, that is, combining traditional and digital methods, has become an integral part of the modern education system. This article provides information on the importance, benefits, challenges, and practical applications of blended learning.